Determination of Phosphoric Acid in the Air of Workplace by Ion Chromatography - Ning, Xia; Zhang, Ji-Hua (Asian Journal of Chemistry, 2012)
In this work, a method is established to determine phosphoric acid in the air of workplace by ion chromatography. The phosphoric acid in the air of workplace was collected with membrane filter and then eluted with water. The eluent was directly injected to the after filtration with 0.22 μm membrane. The signals were detected by ion chromatography with conductivity detector. The separation and determination of the process was completed within 12 min at the flow rate of 1.00 mL/min using the eluent of KOH (30 mmol/L). The retention time of phosphoric acid was 10.507 min. In addition, in the range of 0.50-10.0 μg/mL a good linear relationship was obtained and the correlation coefficient r > 0.999, the detection limit was 0.004 μg/mL and the minimum detectable concentration was 0.003 mg/m3 (to collect 75 L air sample count).